Dysregulation of the epithelial barrier by environmental and other exogenous factors - ÖĞÜLÜR, İSMAİL (WILEY, 2021)
The epithelial barrier hypothesis proposes that the exposure to various epithelial barrier-damaging agents linked to industrialization and urbanization underlies the increase in allergic diseases. The epithelial barrier constitutes the first line of physical, chemical, and immunological defense against environmental factors. Recent reports have shown that industrial products disrupt the epithelial barriers. Innate and adaptive immune responses play an important role in epithelial barrier damage. In addition, recent studies suggest that epithelial barrier dysfunction plays an essential role in the pathogenesis of the atopic march by allergen sensitization through the transcutaneous route. It is evident that external factors interact with the immune system, triggering a cascade of complex reactions that damage the epithelial barrier. Epigenetic and microbiome changes modulate the integrity of the epithelial barrier. Robust and simple measurements of the skin barrier dysfunction at the point-of-care are of significant value as a biomarker, as recently reported using electrical impedance spectroscopy to directly measure barrier defects. Understanding epithelial barrier dysfunction and its mechanism is key to developing novel strategies for the prevention and treatment of allergic diseases. The aim of this review is to summarize recent studies on the pathophysiological mechanisms triggered by environmental factors that contribute to the dysregulation of epithelial barrier function.
Keywords: allergy; asthma; atopic dermatitis; barrier dysfunction; epithelium; rhinitis; sinusitis; type 2 immunity; ELECTRICAL-IMPEDANCE SPECTROSCOPY; ATOPIC-DERMATITIS; RAMAN-SPECTROSCOPY; HUMAN SKIN; ANIONIC SURFACTANTS; FILAGGRIN MUTATIONS; ALLERGIC RHINITIS; PULMONARY-DISEASE; EAACI GUIDELINES; LYMPHOID-CELLS